On Norbert Elias - Becoming a Human Scientist : Edited by Stefanie Ernst - Korte, Hermann (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2017)
The book focuses on the history of Elias' most famous and important work "Process of Civilization" in close relation to the historical and biographical context. It starts with Elias' childhood and intellectual background and paints a detailed picture of the development of German sociology in early 20th century up to the World War 2. Content On Norbert Elias: Becoming a Human Scientist - Prologue - A long Life Has its Advantages - or: The Late Career of a Book - On the Plan of this Academic Work - In Front of the Mirror - Childhood, Youth, Maturation - Old Heidelberg, You Delicate - The First Appearance at the Zurich 'Soziologentag' - The End in Frankfurt - The Great Book - Hoping and Waiting Target Groups Students and researchers of sociology as well as social and cultural sciences. The author Hermann Korte was a Professor of Sociology at the universities Bochum and Hamburg. From 1974 to 2016 he was trustee of the Norbert Elias-Foundation in Amsterdam. He is a member of the P.E.N. Center in Germany. The editor Stefanie Ernst is Professor of Sociology at the University of Münster.